Displacement, social identity and nigrescence in selected contemporary African novels - Ayaicha, Somia (2021)
The bruised voices of the African immigrants in America have been portrayed in contemporary African literature from a more authentic perspective. The depiction of the contemporary African diaspora played a major role at destructing the single story and the stereotypes that the Westerners have built against Africans. Chimamanda Adichie’s Americanah (2013), NoViolet Bulawayo’s We Need New Names (2013) and Imbolo Mbue’s Behold the Dreamers (2016) are among the most recent literary works which mirror the Sub-Saharan immigrants’ journey in contemporary America. Relying on the previously mentioned novels, I am intending to examine the effects of displacement on the African immigrants’ identity as a primary objective in the light of Edward Said, Homi Bhabha and Frantz Fanon’s postcolonial concepts. Based on the experiences of the protagonists, the concepts of displacement, mimicry, otherness and identity is further highlighted due to their immense importance in understanding the mechanism of dealing with the drastic changes after immigration. The second objective is to investigate the impact of the various social identifications and categorizations of the African immigrants using Turner and Tajfel’s Social Identity Theory. In addition, the concept of individual mobility is discussed as a coping mechanism to shed light on the resulting negative social identity. The third objective is to identify the phases that African immigrants go through during the process of becoming black. This latter is analyzed through the Nigrescence Theory by William Cross as it paves the way for a better understanding of the process through which African immigrants start to embrace their black identity. The writers’ portrayal gave voice to the characters and allowed the reader to discover the journey of immigration through the eyes of Africans. This representation was the incentive for conducting this study through the examination of the previously mentioned novel in the light of different theories to build a more compelling analysis. The blend between literary and social psychological theories gave a more in-depth analysis for the fascinating anecdotes which have been studied from the reading of various scholars. The examination of three contemporary diasporic African novels revealed the effects of immigration and to what extent they help in empowering and enhancing the immigrants’ sense of home along with appreciating their blackness and their African culture. Moreover, the study allowed us to fully comprehend their journey from self-hatred to self-acceptance which paved the way for them to embrace their Black identity and increased their Black pride.